Peranan Motivasi dalam Meningkatkan Produktivitas Pegawai di Sekretariat Kantor Bupati Kabupaten Batu Bara - Ahmad Randi Oktavian; Nina Siti Salmaniah Siregar; Maksyum Syahri Lubis (Journal of Education, Humaniora and Social Sciences (JEHSS), 2023)
The aim of this study is to analyze the role of motivation in enhancing employee productivity and its barriers in the Office of the Regent of Batu Bara District. The research utilized a qualitative method with descriptive data analysis. Data were collected through observations, interviews, and documentation. The findings indicate that the interpersonal role is well-established as it encourages employees to develop themselves through training and education. However, the informational role in relation to employee productivity is still low due to some employees' inability to utilize online technology. Additionally, the decisional role of employees is also inadequate, as evidenced by the lack of work discipline. Therefore, there is a need for increased motivation to enhance employee productivity. Efforts required include technology-based training, education, and continuous capacity building of the workforce in technological aspects. Furthermore, intensive socialization regarding the obligations and prohibitions for employees in accordance with Government Regulation No. 53 of 2010 on Civil Servant Discipline is necessary to create an efficient, responsible, authoritative, and capable workforce capable of fulfilling their duties and responsibilities, thus achieving good governance.